Development Aspects of Archaeological Sites in Latvia - Kairišs, Andris; Oļevska, Irina (Archaeologia Lituana, 2021)
Archaeological sites as part of cultural heritage satisfy a broad range of interests of different stakeholders. Along with satisfying cultural, social, scientific, etc., interests, their role is no less important in strategic socio-economic development. Unlocking asocio-economic potential of archaeological sites requires clear vision of how to conserve and protect each particular site, how and by what means to maintain and manage the object as well as what to do with it next. It is widely acknowledged that archaeological sites, in particular those having the status of archaeological monuments, play a socially important role, but their maintenance and development often require significant investment. While the laws make owners of archaeological sites, both private and public, solely responsible for conservation, restoration and maintenance of cultural monuments in their property, there should be appropriate mechanisms that mitigate the financial and legal burden and support owners along the way. Based on the review of legal regulation, scientific literature, information of the authorities and mass media, multiple expert interviews, consultations with professional archaeologists, and using an integrated socio-economic and legal approach to the researched issue, the article provides theoretical and practical insight into the actualities of archaeological heritage development potential in Latvia (making international comparisons) and possible solutions thereto.